Young Amy - Sargent, Dave, 1941-; Sargent, Pat, 1936-; Woodward, Elaine (Prairie Grove, AR : Ozark Pub., 2005)
Amy, a young armadillo practicing her grasshopper catching, becomes lost and meets an unexpected friend.
"A character development book"--Cover.
0.9
K-3
Keywords: Armadillos -- Fiction; Animals -- Infancy -- Fiction; Armadillos -- Fiction; Animal babies -- Fiction